L’introduction de l’hybridation en formation infirmière comme révélatrice des conditions du développement des formateurs - Florence Policard; Emmanuelle Neuville; Margault Sacre; Sabine Petit; Cathy Paulet; Marie-Christine Toczek-Capelle; Guillaume Serres (Recherches en Éducation)
Nursing education, like education in higher education, has made a gradual digital turn, combining face-to-face and distance learning phases, “supported” by an increasingly efficient technical and pedagogical environment. Our study aims to shed light on how trainers of six nursing schools in the same university area implemented this blended approach. Professional development is approached through the prism of trainers' experience and through the characterization of blended courses. This study reveals the profound meaning that trainers attribute to their profession. It underlines through the expression of their experience several obstacles and potentialities in this process.